Det individuella möter det kollektiva. Självbiografiskt stoff i barndomsskildringar från det svenska folkhemmet - Żmuda-Trzebiatowska, Magdalena (Katedra Skandynawistyki UAM, 2011)
The subject of the article are autobiographical threads present in Swedish stories about childhood and adolescence published after 1986 that form part of the narrative pertaining to the origins, evolution and decline of the Swedish welfare state (folkhemmet). With reference to such concepts as autobiographical pact, autobiographical novel and auto-fiction, the author discusses the various ways six contemporary Swedish writers (PC Jersild, Kjell Johansson, Susanna Alakoski, Jonas Gardell and Lena Andersson) use their biographies. Special focus is given to the notion of how a cogitation upon individual fate becomes universal when placed in a social context. Another problem analysed by the author is the significance of autobiographical threads for building relationships between the writer and the reader and for the reception of a literary text.
The Individual Meets the Collective. Autobiographical Threads in Swedish Stories about Childhood
Keywords: självbiografi; den självbiografiska pakten; autofiktion; den självbiografiska romanen; barndomsskildringar; folkhemmet; PC Jersild; Kjell Johansson; Susanna Alakoski; Torbjörn Flygt; Jonas Gardell; autobiography; autobiographical pact; autofiction; autobiographical novel; Swedish welfare state; contemporary Swedish prose